Perceived and misperceived norms about khat and/or cannabis use among adults in southwest Uganda - Perkinsa, Jessica M.; Kakuhikire, Bernard; Baguma, Charles; Meadowsa, Meredith; Evans, Claire Q.; Jurinsky, Jordan; Rasmussen, Justin D.; Satinsky, Emily N.; Ayebare, Patience; Kyokunda, Viola; Juliet, Mercy; Bangsberg, David R.; et al. (International Journal of Drug Policy, 2022)
Background: Studies from high-income contexts have found evidence that norms about substance use are misperceived. The accuracy of perceived norms about khat and cannabis use in Uganda have not previously been described. Methods: We conducted a population-based study targeting all resident adults across eight villages in southwestern Uganda. Personal khat and/or cannabis use frequency was based on self-report. We measured perceived norms about substance use by eliciting individuals’ perceptions about how often most other adult men and most other adult women in their villages used these substances. We compared perceived norms to aggregated village rates of use to assess the extent to which norms were misperceived. We used multivariable Poisson regression to estimate correlates of misperceived norms. Results: Among 1626 participants (91% response rate), only 29 men (4%) and 9 women (1%) reported any lifetime use of khat and/or cannabis. However, 695 participants (43%) did not think lifetime abstinence was the norm among men in their villages, and 256 participants (16%) did not think lifetime abstinence was the norm among women. Moreover, 219 participants (13%) incorrectly believed most men in their village regularly used khat and/or cannabis (≥4 times per week). Misperceived norms were present across subgroups and were correlated with larger social networks, symptoms of depression, loneliness, and younger age Conclusion: In this study of all adults across 8 villages in rural Uganda, many participants misperceived norms about khat and/or cannabis use. Providing accurate information about prevailing norms in the local population may help prevent initiation of khat and/or cannabis use among adults in this context
Keywords: Social norms; Descriptive norms; Peer norms; Social networks; Substance use; Marijuana; Drugs; Sub-Saharan Africa